Limites e potencialidades da transição agroecológica da produção leiteira no território da Cantuquiriguaçu (PR) - Oliveira, Margarete de (2016)
The scenario in which agriculture is inserted today began in the 50s, and was to characterize the use of technologies that have come to revolutionize and enhance the productive systems. All this the basis of so-called technological packages, consisting of pesticides, improved seeds, chemical fertilizers. Decades later began the discussion about the harmful effects that modern agriculture brought with it. In view of this, they have emerged as critical to this model and proposed to seek more sustainable production alternatives, which again included the family farmer, since conventional agriculture was excluded. In the region of Cantuquiriguaçu this discussion is through the CEAGRO, MPA, UFFS, Ecovida Network among others that has been developing incentive and training projects for agroecological practices. In this sense the present study aimed to raise qualitative data regarding the dairy agro-ecological transition in the Territory of Cantuquiriguaçu, in order to analyze the main difficulties and opportunities encountered by farmers in agroecological transition and agroecological dairy producers in the region. Despite initial difficulties with lack of economic resources and the delay in land reclamation and pasture , the use of chemical inputs , adherence to agroecological system has positively to dairy farmers . Considering that after the stabilization of the production system, significant changes such as low cost of milk production, improved health, reduction of pests and diseases in animals , among others.